2013
DOI: 10.1038/jcbfm.2012.212
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Metabolism is Impaired in Transgenic Mice with Tau Hyperphosphorylation

Abstract: In neurodegenerative diseases including Alzheimer's disease and frontotemporal dementia, the protein tau is hyperphosphorylated and eventually aggregates to develop neurofibrillary tangles. Here, the consequences of tau hyperphosphorylation on both neuronal and astrocytic metabolism and amino-acid neurotransmitter homeostasis were assessed in transgenic mice expressing the pathogenic mutation P301L in the human tau gene (pR5 mice) compared with nontransgenic littermate controls. Mice were injected with the neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 38 publications
2
43
0
Order By: Relevance
“…[37][38][39] In addition to the association of hypermetabolism with plaques, a metabolic study in the tau transgenic mouse model of AD showed hypermetabolism in cerebral cortex. 19 Concluding Remarks The major finding of this study is the hypermetabolic state in the 7-month-old 3xTg-AD mice as compared with age-matched nonTg mice and these results are in contrast to the hypometabolism observed in 13-month-old 3xTg-AD mice. Importantly, the specific role of metabolism in the coordinated picture of hyperactivity (electrophysiologic and physiologic), previously reported in multiple mouse models of AD was highlighted.…”
Section: Effect Of Lipoic Acidmentioning
confidence: 64%
“…[37][38][39] In addition to the association of hypermetabolism with plaques, a metabolic study in the tau transgenic mouse model of AD showed hypermetabolism in cerebral cortex. 19 Concluding Remarks The major finding of this study is the hypermetabolic state in the 7-month-old 3xTg-AD mice as compared with age-matched nonTg mice and these results are in contrast to the hypometabolism observed in 13-month-old 3xTg-AD mice. Importantly, the specific role of metabolism in the coordinated picture of hyperactivity (electrophysiologic and physiologic), previously reported in multiple mouse models of AD was highlighted.…”
Section: Effect Of Lipoic Acidmentioning
confidence: 64%
“…A short period infusion of acetate has been used to evaluate energy metabolism of astrocytes in many studies (Chowdhury et al 2012;Nilsen et al 2013). In fact, the labeling of glutamine-C4 from 15 min of [2- 13 C]acetate infusion in this study is~12%, which is significant amount to identify ethanol-related alteration in the astroglial flux.…”
Section: Effect Of Ethanol On Astroglial Activitymentioning
confidence: 78%
“…These results further substantiate the metabolic alterations present in the different Alzheimer's disease rodent models. [30][31][32][33] Magnetic resonance studies conducted in the APP-PS1 model of Alzheimer's disease show decreased NAA and Glu, 30 along with an increase of MI. 34 A systematic evaluation on the APP-PS1 model found the ratio of choline to creatine (in the cortical and subcortical areas) as a noninvasive biomarker in these mice but did not find the utility of Glu, Gln, and MI as biomarkers.…”
Section: Enrichment Of Glu Gln and Aspmentioning
confidence: 99%